2017
DOI: 10.1021/acsomega.7b00714
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Complexes of C-Substituted Cyclams and Their Activity for CO2 and H+ Reduction

Abstract: Several nickel(II) complexes of cyclams bearing aryl groups on the carbon backbone were prepared and evaluated for their propensity to catalyze the electrochemical reduction of CO 2 to CO and/or H + to H 2 , representing the first catalytic analysis to be performed on an aryl–cyclam metal complex. Cyclic voltammetry (CV) revealed the attenuation of catalytic activity when the aryl group bears the strong electron-withdrawing trifluoromethyl su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…The selected electrolysis potential resulted in lower FE but higher TOF for Ni II (MPC) and Ni II (cyclam) compared to our previous report . While each experiment showed significant and highly variable H 2 production, a catalyst‐free CPE experiment revealed that the H 2 production is mostly due to the background current instead of the catalysts.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…The selected electrolysis potential resulted in lower FE but higher TOF for Ni II (MPC) and Ni II (cyclam) compared to our previous report . While each experiment showed significant and highly variable H 2 production, a catalyst‐free CPE experiment revealed that the H 2 production is mostly due to the background current instead of the catalysts.…”
Section: Resultsmentioning
confidence: 53%
“…They all share the common features of the loss of reversibility for the Ni(+1/+2) couple, significant increase in current and the growth of an additional reduction peak at more negative potentials. These features are indicative of catalytic reduction of CO 2 . Furthermore, while the catalytic currents at –1.76 V are about the same for 1 (56 µA) and Ni II (MPC) (49 µA), it is nearly doubled for 2 (96 µA).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…While these configurations may change upon reduction of Ni70 and Ni71 to their Ni + active species, this example shows how minor changes in ligand structure can have a dramatic effect on catalytic activity. 473…”
Section: Homogeneous Catalysismentioning
confidence: 99%